Gerakan Nasionalisme Islam Sebelum Kemerdekaan RI - Mawar Febrianti (SIASAT, 2018)
Nationalism among Indonesian Muslims has grown since a number of sultans in the homeland against the Dutch. The resistance of the empire was a physical war against the Dutch. After the Dutch conquered almost all local sultanates and kingdoms, so that the Dutch controlled Indonesia completely, the form of resistance then changed. Changes in the form of struggle are marked by the birth of Islamic movements, both in the form of madrasa (schools), mass organizations, and political parties. Awareness of the spirit of nationalism was formed from the age of the empire, which then continued to grow among Islamic mass organizations, eventually becoming more crystallized within the bodies of political parties.